Advances in Rheology of Materials - Dutta, Ashim; Muhamad Ali, Hafiz (IntechOpen, 2023)
In modern times, rheology has emerged as a powerful tool for materials scientists to explore the properties of soft matter or complex fluids, including such diverse materials as food, cosmetics, polymers, lubricants, drilling fluids and biological systems. Rheology parameters such as shear modulus (G'), storage modulus (G") and viscosity (η), together with microscopic imaging, provide considerable insight into the structure-property relationship in these materials. This in turn helps design materials with properties tailored to multiple applications. This book is a compilation of works by experts in their respective areas of specialization and covers a wide range of applications. The book will be useful both to experts in this area of research and to newcomers from a range of specializations.